Can Mean Platelet Volume be a New Risk Factor in Portal Venous Thrombosis?. (July 2013) - Aliosmanoglu, Ibrahim; Gul, Mesut; Oguz, Abdullah; Basol, Omer; Uslukaya, Omer; Keles, Celalettin
Background: The aim of this study was to discuss the possibility of mean platelet volume (MPV) being a new risk factor in the etiology of portal venous thrombosis (PVT).Methods: Study participants were categorized into 2 different groups: group I, control group (n = 35) and group II, PVT group (n = 34). Demographic data and MPV values were recorded retrospectively.Results: No differences were determined between the 2 groups regarding hypertension, diabetes mellitus, and smoking ( P > .05). The average hemoglobin levels were 10.8 ± 2.1 in group II and 14.0 ± 1.7 in group I ( P < .001). Although the MPV levels of group II patients were 8.2 ± 0.52, the average level in group I was determined as 7.8 ± 0.62 ( P = .012). In the performed receiver–operating characteristic (ROC) analysis, the cutoff value for patients with PVT for MPV was determined as 7.9 (area under curve: 0.674), sensitivity as 70.6%, and specificity as 65.7% ( P = .013).Conclusion: The current study shows that MPV is significantly higher in patients with PVT than in the control group.